A Study of Brand Preference and Consumption Pattern of Beer in Bareilly - Gupta, Manish (Indian Journal of Marketing, 2013)
The present paper is an attempt to understand how brand preferences and consumption pattern of beer changes across demographic and other variables and more importantly, which product attributes are associated with these changes. The purpose of this paper is to investigate the various factors of brand preference towards beer, and additionally, it also throws some light on the behavioural aspects of the consumers such as frequency of consumption of an alcoholic beverage - beer. In this paper, respondents were selected randomly, and the data was analyzed and interpreted with the help of SPSS software. Hypotheses framed for the research work have been tested with the help of the chi- square test to measure the variance and to accept or reject the null hypothesis. This study made a methodical effort of studying brand preference and consumption pattern of beer by analyzing the factors associated with brand preference - frequency of beer consumption amongst beer drinkers, studying the effect of demographic variables on specific brand choice, and analyzing the relationship between monthly income of the respondents and their expenditure on beer. The study reveals that demographic variables have a significant impact on brand preference and consumption pattern of beer. It can also act as a powerful tool for marketers for strategy determination in the areas of beer production and management, marketing, brand positioning, pricing policy, and distribution.